STRESS ON SPUR GEAR AND SIMULATION FOR MICRO HYBRID SYSTEMS BY ANSYS WORKBENCH - Anisul Islam; Md. Mashrur Islam (Universitas Pendidikan Indonesia, 2019)
Spur gears are the most well-known kind of gears used in hybrid vehicle’s power transmission. They have straight teeth, and are mounted on parallel shafts. In some cases, many spur gears are utilized without a moment's delay to make huge rigging decreases. In this paper how stress creates on a spur equip under various conditions and conditions and reenactments of a rigging system (two spur gears) is assessed by Ansys workbench. For this static structural and dynamic analysis modeling is utilized. A couple of spurs equip tooth in real life is by and large subjected to two sorts of cyclic stress: contact stress and twisting stress including bowing fatigue. The two stresses may not accomplish their greatest esteems at a similar purpose of contact fatigue. These sorts of failure can be limited by analysis of the issue amid the outline organize and making appropriate tooth surface profile with legitimate assembling strategies.